Biomarkers as pollution indicators with special reference to cetaceans - Peakall, D. (J. Cetacean Res. Manage., 1999)
The limited information available on biomarkers in cetaceans and pinnipeds is reviewed. The main problems with their application to cetaceans are the difficulties in obtaining suitable tissue material and in carrying out experimental work to relate pollutant levels and effects. A white whale population from the Gulf of St Lawrence has been found to have a high incidence of tumours and the presence of adducts was related to exposure to benzo(a)pyrene (PAH), a well known carcinogen. Some research has been carried out on induction of Mixed Function Oxidases (MFOs) (mainly cytochrome P450 system) in cetaceans, but the results are not yet conclusive. Studies on other groups of animals suggest that MFOs may be valuable biomarkers, particularly if techniques to measure them in biopsy skin samples are further developed. The goal should be that wild cetaceans are physiologically normal, biomarkers can be used to identify populations whose physiological functions are outside normal limits because of excessive exposure to pollutants. Since no pristine environments currently exist, measurements of biomarkers along gradients of pollutant exposure are needed to establish physiological normality in cetaceans.